2001
DOI: 10.1128/iai.69.5.2797-2807.2001
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Augment Bacterial Species- and Strain-Dependent Induction of Tissue Factor Activity in Bacterium-Infected Human Vascular Endothelial Cells

Abstract: In bacterial endocarditis (BE), intravascular infection with Staphylococcus aureus, Streptococcus sanguis, orStaphylococcus epidermidis can lead to formation of a fibrin clot on the inner surface of the heart and cause heart dysfunction. The events that start the coagulation in the early stage of the disease are largely unknown. We have recently shown that human endothelial cells (EC) upon binding and internalization of S. aureus, but not S. sanguis or S. epidermidis, express tissue factor (TF)-dependent proco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 45 publications
7
89
0
Order By: Relevance
“…Several environmental factors have been identified, such as strong inducers of TF gene expression, including viruses, 44 bacteria, [45][46][47] other microbial pathogens such as cytomegalovirus, Chlamydia pneumoniae, Streptococcus sanguis and Plasmodium falciparum, [48][49][50] endotoxin 51 and oxidative air pollutant particulate matter. 52 In this study, we showed that the G allele in the À603 position is associated with a higher promoter activity than the A allele in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors have been identified, such as strong inducers of TF gene expression, including viruses, 44 bacteria, [45][46][47] other microbial pathogens such as cytomegalovirus, Chlamydia pneumoniae, Streptococcus sanguis and Plasmodium falciparum, [48][49][50] endotoxin 51 and oxidative air pollutant particulate matter. 52 In this study, we showed that the G allele in the À603 position is associated with a higher promoter activity than the A allele in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the valve stromal cell to the blood induced PCA following interaction with lipopolysaccarides (LPS) and IL-l. Induction of tissue factor activity (TFA) by bacteria mainly depends on their ability to internalize within the endothelial cell (12) Bacterial colonization within the vegetation tPMP Once there is activation of the coagulation system and the inflammatory response, host defense mechanisms are activated against the invading bacteria. Activated platelets are capable of secreting thrombin that induces platelets microbiocidal peptides production (tPMP) (13).…”
Section: Procoagulant Activity Following Endothelial Cell Injurymentioning
confidence: 99%
“…Exposure to inflammatory agents, however, quickly upregulates TF expression in these vascular cell types. Induction of TF expression on monocytes and endothelial cells has been linked to the pathology of a number of diseases [5][6][7]. In addition, TF-bearing circulating microparticles of endothelial origin may contribute to the pathology of acute coronary syndromes [8].…”
Section: Introductionmentioning
confidence: 99%